Monitoring and determination of CO2 by using optical fibre sensor and artificial neural network / Faiz Bukhari Mohd Suah, Abdul Mutalib Md Jani and Siti Aminah Md Ali - Mohd Suah, Faiz Bukhari; Md Jani, Abdul Mutalib; Md Ali, Siti Aminah (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
Optical fibre carbon dioxide sensors with a dip-coated sol-gel film containing indicator dye of thymol blue are prepared and characterized The sensitive film has both organic and Inorganic parts with good gas permeability. The difference between attenuations In N2 gas and In C02/N2 mixture gas increases with the increase in the CO2 concentration in the 0 55 o7IJm range The attenuation difference increases linearly with the increase in the log of CO? concentration, although there is no difference under 0 1% CO2 gas concentration The sensitivity of the sensor increases with the increase in the dye concentration The relative humidity and the film composition have an important effect on the attenuation difference The application of artificial neural network (ANN) in signal processing of optical fibre pH sensor is presented The pH sensor is developed based on the use of bromophenol blue indicator immobilized in a sol-gel thin film as a sensing material A three layer feed-forward network was used and the network training was performed using the back-propagation (BP) algorithm Spectra generated from the pH sensor at several selected wavelengths are used, as the input data for the ANN. The bromophenol blue indicator, which has a limited dynamic range of 300-550 pH units, was found to show higher pH dynamic range of 200-1200 and with low calibration error after training with ANN The enhanced ANN could be used to predict the new measurement spectra from unknown buffer solution with an average error of 006 pH units. Changes of ionic strength showed minor effect on the dynamic range of the sensor The sensor also demonstrated good analytical performance with repeatability and reproducibility characters of the sensor yield relative standard deviation (RSD) of 6 ± 0.22 and 6 ± 0 32, respectively Meanwhile the RSD value for this photostability test is pH 7 ± o 19 and it demonstrated no hysteresis when the sensor was cycled from pH 2 00- 12 002 00 (acid- base- acid region) of different pH Performance tests demonstrated a response time of 15 - 150 seconds, depending on the pH and quantity of the immobilized Indicator